2018
DOI: 10.1158/0008-5472.can-17-0385
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Long Noncoding RNA YIYA Promotes Glycolysis in Breast Cancer

Abstract: Long noncoding RNA (lncRNA) is yet to be linked to cancer metabolism. Here, we report that upregulation of the lncRNA () promotes glycolysis, cell proliferation, and tumor growth in breast cancer. YIYA is associated with the cytosolic cyclin-dependent kinase CDK6 and regulated CDK6-dependent phosphorylation of the fructose bisphosphatase PFK2 (PFKFB3) in a cell-cycle-independent manner. In breast cancer cells, these events promoted catalysis of glucose 6-phosphate to fructose-2,6-bisphosphate/fructose-1,6-bisp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 33 publications
0
53
0
Order By: Relevance
“…Similar to many other lncRNAs, AGPG has tissue-specific expression patterns in different cancers 14 . Next, we performed qRT-PCR and RNAScope in situ hybridization (ISH) assays to detect AGPG expression in ESCC, GC, and CRC tissues 15 . Our results showed that AGPG was highly expressed in ESCC, GC, and CRC tissues ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to many other lncRNAs, AGPG has tissue-specific expression patterns in different cancers 14 . Next, we performed qRT-PCR and RNAScope in situ hybridization (ISH) assays to detect AGPG expression in ESCC, GC, and CRC tissues 15 . Our results showed that AGPG was highly expressed in ESCC, GC, and CRC tissues ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We compared the AGPG-binding proteins with antisense AGPG-binding proteins. Proteins that bound to antisense AGPG were excluded from the candidate list, and the remaining proteins were sorted by MS score, as described in previous lncRNA studies 15 . We found that sense AGPG, but not the antisense control, interacted specifically with PFKFB3 ( Fig.…”
Section: Escc Gc Crcmentioning
confidence: 99%
“…YIYA or linc00538 increases 6-phosphofructo-2-kinase/ fructose-2, 6-biphosphatase 3 (PFKFB3) enzymatic activity through CDK6-dependent phosphorylation, thereby enhancing the conversion of G6P/F6P to FBP/GBP. Increased expression of YIYA and CDK6 maintain elevated glycolysis in breast cancer, thus disfavoring patients' survival [79]. LncRNA IDH1 antisense RNA1 (IDH1-AS1) enhances IDH1 enzymatic activity at post-translational level by facilitating IDH1 homodimerization, resulting in increased production of α-ketoglutarate (α-KG) as well as downregulation of ROS [80,81].…”
Section: Lncrnas Regulate Glucose Metabolismmentioning
confidence: 99%
“…On the other end of the spectrum, deletion of a 1.1-Mbp region on the human chromosome 6 containing a cluster of vlincRNAs in a fibrosarcoma cell line also using CRISPR/Cas9 has implicated one of them, vlinc273 or ASAR6-141, in control of replication timing of that chromosome [118]. In fact, lncRNA knockouts using genome-editing techniques in cultured cell models implicated lncRNAs in metabolism control [119,120], cell growth [119,[121][122][123], metastasis [124], and migration and invasion of human cancer cells [119,122,123,125].…”
Section: Genome Targetingmentioning
confidence: 99%